An Analysis of Power Relations and Emotional Imbalance in the Song Manchild by Sabrina Carpenter through Feminist Criticism - Zaskia Naura Rianto; Nadhillah Tsaqif; Mumtaz Naurah; Novalini Annisa Fitri; Nazira Ade Ifana Br Harahap; T. Thyrhaya Zein (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study analyzes power relations and emotional imbalance in the song “Manchild” by Sabrina Carpenter through feminist literary criticism. Emotional inequality in patriarchal relationships remains an important issue, but emotional dependency as a form of patriarchal domination is still rarely discussed in popular music studies. Therefore, this study aims to identify the representation of patriarchal power and unequal emotional labor in the lyrics and examine the female narrator’s resistance to traditional gender expectations. This study employs a qualitative literary criticism approach using the song lyrics as the primary data source. The data were analyzed through textual analysis and thematic interpretation based on feminist literary criticism, focusing on Simone de Beauvoir’s concept of “the Other” and Kate Millett’s theory of patriarchy to interpret representations of power relations and emotional imbalance within the lyrics. The findings reveal that the male figure depends emotionally on the female narrator while avoiding responsibility, causing unequal emotional labor. Patriarchal domination also operates subtly through emotional dependency, while the female narrator expresses resistance through sarcasm, irony, and criticism. Therefore, Manchild functions not only as a feminist critique of emotional inequality and patriarchal relationship patterns but also contributes to feminist literary scholarship by demonstrating the value of contemporary popular music as a cultural text for examining gendered power relations, emotional labor, and patriarchal ideology in modern society.